Análisis y clasificación de las urgencias hospitalarias mediante los Ambulatory Patient Groups Analysis and classification of hospital emergencies through Ambulatory Patient Groups - A. Conesa; L. Vilardell; R. Muñoz; J.M. Casanellas; P. Torre; G. Gelabert; A. Trilla; M.A. Asenjo (Elsevier, 2003)
Objetivo: Describir la factibilidad y el resultado de la aplicación del sistema Ambulatory Patient Groups (APG) a la casuística atendida en los servicios de urgencias de seis hospitales del área de Barcelona. Métodos: Confección de un conjunto mínimo básico de datos específico para urgencias (CMBDAU). Obtención de las variables necesarias en una muestra aleatoria de visitas atendidas, a partir de los informes de asistencia correspondientes. Aplicación del sistema APG a los episodios seleccionados. Resultados: Se ha codificado y agrupado en APG un total de 11.188 visitas de urgencias. Quince diagnósticos identifican el 25% de los episodios. El 50% de los procedimientos de urgencias son exploraciones complementarias sencillas. Quince APG agrupan el 50% de la casuística atendida en urgencias. Conclusiones: El CMBDAU es válido para describir la casuística de urgencias y su agrupación en APG proporciona resultados consistentes e interpretables. La aplicación generalizada de sistemas como los APG en urgencias requiere una validación previa en nuestro entorno de los valores de peso norteamericanos. También debe valorarse la disponibilidad de recursos técnicos y humanos suficientes para garantizar la calidad y la continuidad de un registro de estas características. Aim: To assess the feasibility and results of application of Ambulatory Patient Groups (APG) patient's classification system to the case-mix of patients seen at the Emergency Departments (ED) of 6 Barcelona metropolitan area hospitals. Methods: Development of a minimum discharge data set specific for the Emergency Departments (CMBDAU). Gathering of relevant variables from a random sample of patients seen at the ED using the ED discharge reports. Use of the APG classification system to those episodes. Results: A total of 11.188 episodes were codified and grouped with the APG system. Fifteen diagnostics identified 25% of all episodes. Nearly 50% of all procedures performed at the ED were common and simple procedures. Fifteen APG's grouped 50% of all cases seen at the ED. Conclusions: The ED Uniform Discharge Data Set (CMBDAU) developed is a valid instrument for describing the case-mix seen at the ED, and its grouping by means of the APG system provides consistent and meaningful results. The widespread use of systems like APG in the ED requires a former validation of relative weights assigned in the US system. The availability of human and technical resources must also be assessed, in order to guarantee the quality and sustainability of such a system.